2021
DOI: 10.3390/agronomy11112341
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Impact of Biochar and Arbuscular Mycorrhizal on Root Morphology, Physiological Properties of Fenugreek (Trigonella foenum-graecum L.) and Soil Enzymatic Activities

Abstract: Arbuscular mycorrhizal fungi (AMF) inoculation and biochar amendment has been reported to improve the growth of several crop plant; however, their role in stress amelioration individually as well as in combination has not been worked out. Limited information is available about the synergistic use of biochar and Arbuscular Mycorrhizal Fungi (AMF). Here, we investigated the synergistic effect of biochar and AMF on plant development, root architecture, the physiological performance of fenugreek (Trigonella foenum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 99 publications
2
9
0
1
Order By: Relevance
“…Data regarding AMF alone treatment improved plant growth (the number of leaves, length of leaves, and width of leaves). Numerous studies have presented AMF-promoted plant development, plant nutrition, and yield. , Similarly, Kumar reported that AMF improved plant growth parameters in Jatropha curcas L. These results are consistent with the findings obtained by Yamawaki et al who investigated that the application of AMF enhanced plant height, number of leaves, and number of stems in turmeric ( Curcuma longa L) than that in control treatment, respectively. Similar findings were informed by Chen single AMF significantly improved leaf area, plant height and the total biomass in Catalpa bungei C.A.Mey.…”
Section: Discussionsupporting
confidence: 87%
“…Data regarding AMF alone treatment improved plant growth (the number of leaves, length of leaves, and width of leaves). Numerous studies have presented AMF-promoted plant development, plant nutrition, and yield. , Similarly, Kumar reported that AMF improved plant growth parameters in Jatropha curcas L. These results are consistent with the findings obtained by Yamawaki et al who investigated that the application of AMF enhanced plant height, number of leaves, and number of stems in turmeric ( Curcuma longa L) than that in control treatment, respectively. Similar findings were informed by Chen single AMF significantly improved leaf area, plant height and the total biomass in Catalpa bungei C.A.Mey.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Zulfiqar et al (2021b) reported improved growth characteristics (plant height, tiller number, shoot diameter, and leaf number) in an important medicinal plant, A. zerumbet, in response to wheat straw-based BC alone and combined with compost. Jabborova et al (2021a) found that BC application improved plant height, leaf length, leaf number, and leaf width in sweet basil relative to control plants. Wang et al (2019) reported improved plant height, root and shoot dry weights, and root/shoot ratio in apple seedlings in response to different BC doses.…”
Section: Biochar Improves Horticultural Crop Growth Yield and Produce...mentioning
confidence: 93%
“…Likewise, BC and humic acid treatments improved chlorophyll content in calendula ( Calendula officinalis L.) compared to controls ( Karimi et al., 2020 ). In fenugreek ( Trigonella foenum-graecum ), Jabborova et al. (2021a) reported that BC increased chlorophyll pigments by 30% and carotenoids by 60%.…”
Section: Biochar Alters Phytohormones and Improves The Photosynthesis...mentioning
confidence: 99%
“…In addition, they stimulate the production of endogenous phytohormones and antioxidants. The higher rate of photosynthesis that results from light harvesting in a symbiotic connection may explain this phenomenon (Wu et al, 2010;Jabborova et al, 2021). The PLS-SEM results proved that the increase in growth, and yield was due to photosynthetic pigments (path coe cient = 1.036, p < 0.05) proved by (Fig.…”
Section: Discussionmentioning
confidence: 86%